RELATIONSHIP OF URDU LANGUAGE WITH POWER IN PERSPECTIVE OF LINGUISTIC, SOCIAL, AND CULTURAL DOMINANCE - Hina Saleem; Saifullah Zafar; Ayra Tariq (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
In this study, the researcher aims to highlight the relationship between language and power from the perspective of social, cultural, and linguistic power that language gives to individuals and groups. Language is a tool to get power, and in the contemporary world, people are getting influenced by others through solid language skills. However, to understand the relationship between language and power, we first need to define these terms separately and then come towards the relationship between them. Such as, language is a system of communication used by people in a particular society, community, or/or country. At the same time, power is an influence that individuals or groups have over their followers. Therefore, power is determined by the followers. Hence, the people get four types of power through language; single word power, communitive power, narrative power, and authoritative power. Moreover, in Pakistan Urdu language is a state language, and the community that uses the Urdu language is considered elite class people and shows their language power over the speakers of other languages.